Familial Hypercholesterolemia: A Systematic Review of Guidelines on Genetic Testing and Patient Management - Migliara, Giuseppe; Baccolini, Valentina; Rosso, Annalisa; D’Andrea, Elvira; Massimi, Azzurra; Villari, Paolo; De Vito, Corrado (Frontiers in Public Health, 2017)
Background Familial hypercholesterolemia (FH) is an autosomal-dominant hereditary disorder of lipid metabolism that causes lifelong exposure to increased LDL levels resulting in premature coronary heart disease and, if untreated, death. Recent studies have shown its prevalence to be higher than previously considered, which has important implications for the mortality and morbidity of associated cardiovascular disease (CVD). Several clinical tools are used worldwide to help physicians diagnose FH, but nevertheless most patients remain undetected. This systematic review of guidelines aims to assess the role of genetic testing in the screening, diagnosis, and management of patients affected by heterozygous or homozygous FH and to identify related health-care pathways. Methods We performed a systematic review of the literature; inclusion criteria were English or Italian guidelines focusing on genetic testing. The guidelines were included and evaluated for their content and development process using the Appraisal of Guidelines for Research and Evaluation II instrument. Results Ten guidelines were considered eligible, and all were judged to be of good quality, with slight differences among them. The most common indications for performing genetic tests were high levels of cholesterol, or physical findings consistent with lipid disorder, in the subject or in the family history. Subsequent screening of family members was indicated when a mutation had been identified in the index patient. Regarding patient management, the various guidelines agreed that intensive treatment with lipid-lowering medications should begin as quickly as possible and that lifestyle modifications should be an integral part of the therapy. Conclusion Since the early detection of affected patients is beneficial for effective prevention of CVD, genetic testing is particularly useful for identifying family members via cascade screening and for distinguishing between heterozygous and homozygous individuals, the latter of which require more extreme therapeutic intervention.